Partial Least Squares Structural Equation Modeling (PLS-SEM): the influence of autonomy and relatedness on student competence in English learning - Sahara, Erista; Fahira, Naila; Kholifah, Siti (LEOTECH: Journal of Learning Education and Technology, 2024)
This study aims to examine the influence of psychological factors of autonomy, relatedness on improving academic competence in learning English among elementary school students. This study used a quantitative approach with survey method and used Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. The sample consisted of 240 students from three primary schools in Cirebon consisting of SDN 2 Kedungdawa, SDN Karang Mulya, and SDN Sukasari in grades IV, V and VI. Data were collected through a validated and reliable Likert scale questionnaire measuring the three factors of autonomy, relatedness, and competence. Results showed that the autonomy factor has a positive influence on students' competence in learning English. The findings highlight the importance of considering psychological aspects in designing effective English learning strategies for young learners to improve students' competence and learning outcomes.